Combined Beneficial Effect of Genistein and Atorvastatin on Adipogenesis in 3T3-L1 Adipocytes - Lee, Dahae (Biomolecules, 2021)
Genistein (4,5,7-trihydroxyisoflavone) is abundant in various dietary vegetables, especially soybeans, and is known to have not only an estrogenic effect but also an antiadipogenic effect. Atorvastatin (dihydroxy monocarboxylic acid) is a statin used to prevent heart disease. Although genistein and atorvastatin have been reported to possess antiadipogenic effects, their combined effects are still unclear. The aim of the current study was to explore whether the combination of genistein and atorvastatin at low concentrations significantly suppresses adipogenesis in a murine preadipocyte cell line (3T3-L1) compared to treatment with genistein or atorvastatin alone. Our results showed that cotreatment with 50 µM genistein and 50 nM atorvastatin significantly suppressed preadipocyte differentiation, whereas when each compound was used alone, there was no inhibitory effect. Additionally, cotreatment with genistein and atorvastatin significantly downregulated adipogenic marker proteins, including mitogen-activated protein kinases (MAPKs), peroxisome proliferator-activated receptor γ (PPARγ), CCAAT/enhancer-binding protein alpha (C/EBPα), glucocorticoid receptor (GR), and CCAAT/enhancer-binding protein β (C/EBPβ). This is the first evidence of the combined antiadipogenic effects of genistein and atorvastatin. Although additional experiments are required, combinational treatment with genistein and atorvastatin may be an alternative treatment for menopause-associated lipid metabolic disorders and obesity.